'What I really want is academics who want to partner and who care about the outcome': findings from a mixed-methods study of evidence use in local government in England. (5th February 2023) - Cheetham, Mandy; Redgate, Sam; van der Graaf, Peter; Humble, Clare; Hunter, David; Adamson, Ashley
Abstract : Background: Local government (LG) is ideally placed to influence the determinants of public health (PH) and reduce inequalities, but opportunities are routinely missed. Aims and objectives: The aim of the Local Authority Champions of Research (LACoR) study was to explore ways to embed a culture of evidence use in LG. Methods: Five linked work packages were undertaken using mixed methods. In this paper, we report data from semi-structured interviews with UK local authority (LA) staff (n=14). Findings: Findings show a changing culture of LG: embedded researchers can enhance connectivity and interaction, build linkages, use levers of influence, and learn alongside LG navigators. Understanding the diverse microcultures of evidence use in LG is critical. Research champions can help to navigate the social, financial, political and regulatory context of LG and academia, influencing change dynamically as opportunities emerge. Discussion: Changing organisational subcultures is ambitious and unpredictable given the complexities of, and variability in, local contexts. Cumulative changes appear possible by recognising existing assets, using relational approaches to respond to LG priorities. In-house capacity remains underestimated and underutilised in efforts to embed evidence use in LG decision making. Co-located embedded researchers can use contextually specific knowledge and relationships to enhance evidence use in LG in collaboration with system navigators. Conclusions: There is a need for academics to adapt their approach, to take account of the context of LG to achieve meaningful health and social impacts with LG and test the contribution of embedded approaches to wider system change.